Laser surface modification of Cr-MO powders on grey cast iron for surface properties improvement - Zulhishamuddin, Abd Rahman (2018)
Recently, in industrial area, grey cast iron component parts (such as cylinder liner and break disc) experienced wear defect and corrosion due to the usage in high temperature, pressure and mechanical friction, which contribute to multifaceted, high-stress condition. The purpose of this research is to develop a modified surface layer on grey cast iron using laser melting and laser cladding. To strengthen the surface, Cr-Mo powder were added on the surface. The parameter on this process were analyzed using statistical analysis. The presented work is an investigation and modification of the laser surface of grey cast iron using pulse laser processing mode. Initial screening experimental designs was conducted and lead to more optimized detailed designs. A laser Nd:YAG system 300HPS model with 10.64 μm wavelength was used. Preliminary experiment of design of experiment 2-level factorial model were conducted in laser surface melting grey cast iron with spot size 1.0 mm, 1.2 mm, 1.4 mm and 1.7 mm to investigate optimized laser parameter and suitable spot size for the surface geometry, surface roughness and hardness. Based on the optimization laser parameter in laser surface melting, laser spot size of 1.0 mm with PP , PRF and S in range of 800 to 1200 W, 80 to 90 Hz and 19.2 to 21.6 mms-1 were used in laser surface cladding respectively. A comprehensive experiment that combines mixture components of Cr and Mo with process factor were used in laser surface cladding. The laser processing was constantly assisted by in line argon gas at 10 Lmin-1. Laser processed samples were prepared for metallographic study and were characterized for physical and mechanical properties. The metallographic study and chemical composition analysis were conducted using scanning electron microscope integrated with energy dispersive x-ray spectroscopy. The crystallinity and phase detection of the modified surface were conducted using an XRD system with Cu Kα radiation and wavelength of 1.54 Å. The surface profile was measured using stylus profilometry measuring systems. The hardness properties of the modified surface were measured by micro-Vickers diamond indentation. A modified surface layer (Cr-Mo mixture added) had shown the elimination of graphite and a new structure of dendritic with the formation of particles in size of 32 nm had developed. A new phase of carbide was also detected on the surface which mainly contained of M2C, M3C2 and M23C6. A maximum hardness modified grey cast iron of 1039.7 HV0.1 is achieved at laser surface cladding parameter at 1200 W, 80 Hz and mixture of 32.3 % Cr and 67.7 % Mo. Another important finding was that wear resistance increases by adding the mixture of Cr and Mo on the grey cast iron surface. A relationship between laser surface parameter and mixture of Cr and Mo was established for further understanding of the effects of the laser parameters. These findings are significant to the establishment of surface hardening technique for wear resistance, oxidation and thermal resistance for cylinder liner and break disc.